Paradox [compact disc, unabridged] - Coulter, Catherine (The FBI thrillers, 2018)
When divers discover the bones of multiple murder victims during a search of Lake Massey, agents Sherlock and Savich make a connection between the bones and an escaped psychopath who attempted to kidnap five-year-old Sean Savich.